Terapi Hiperbarik Oksigen sebagai Tata Laksana Tuli Mendadak: Tinjauan Pustaka - Widjaja, Gabriela (PT Kalbe Farma Tbk., 2025)
Sudden deafness or sudden sensorineural hearing loss is sensorineural deafness which is an ENT emergency because it can become permanent if not treated immediately. Sudden deafness is characterized by a sensorineural hearing loss of at least 30 dB within less than 72 hours. Most causes of sudden deafness are unknown (idiopathic) so treatment is empirical. The principles of managing sudden deafness are early detection, early diagnosis, and early treatment. The main treatment for sudden deafness is oral steroids, intratympanic, or a combination of both. Hyperbaric oxygen therapy (HBOT) has become a promising adjuvant therapy, working by increasing oxygenation in the perilymph and ischemic cochlear tissue. Several studies have shown that combining HBOT with steroids provides superior results compared to steroid monotherapy, especially in cases of severe deafness and if started within two weeks of symptom onset. Further research is still needed to confirm the effectiveness of hyperbaric oxygen therapy as a treatment for sudden deafness.